Process evaluation of a cluster randomised controlled trial to improve bronchiolitis management - a PREDICT mixed-methods study. - Haskell L; Tavender EJ; O'Brien S; Wilson CL; Babl FE; Borland ML; Schembri R; Orsini F; Cotterell E; Sheridan N; Oakley E; Dalziel SR; et al. (BioMed Central Ltd)
BACKGROUND: Bronchiolitis is the most common reason for hospitalisation in infants. All international bronchiolitis guidelines recommend supportive care, yet considerable variation in practice continues with infants receiving non-evidence based therapies. We developed six targeted, theory-informed interventions; clinical leads, stakeholder meeting, train-the-trainer, education delivery, other educational materials, and audit and feedback. A cluster randomised controlled trial (cRCT) found the interventions to be effective in reducing use of five non-evidence based therapies in infants with bronchiolitis. This process evaluation paper aims to determine whether the interventions were implemented as planned (fidelity), explore end-users' perceptions of the interventions and evaluate cRCT outcome data with intervention fidelity data. METHODS: A pre-specified mixed-methods process evaluation was conducted alongside the cRCT, guided by frameworks for process evaluation of cRCTs and complex interventions. Quantitative data on the fidelity, dose and reach of interventions were collected from the 13 intervention hospitals during the study and analysed using descriptive statistics. Qualitative data identifying perception and acceptability of interventions were collected from 42 intervention hospital clinical leads on study completion and analysed using thematic analysis. RESULTS: The cRCT found targeted, theory-informed interventions improved bronchiolitis management by 14.1%. The process evaluation data found variability in how the intervention was delivered at the cluster and individual level. Total fidelity scores ranged from 55 to 98% across intervention hospitals (mean = 78%; SD = 13%). Fidelity scores were highest for use of clinical leads (mean = 98%; SD = 7%), and lowest for use of other educational materials (mean = 65%; SD = 19%) and audit and feedback (mean = 65%; SD = 20%). Clinical leads reflected positively about the interventions, with time constraints being the greatest barrier to their use. CONCLUSION: Our targeted, theory-informed interventions were delivered with moderate fidelity, and were well received by clinical leads. Despite clinical leads experiencing challenges of time constraints, the level of fidelity had a positive effect on successfully de-implementing non-evidence-based care in infants with bronchiolitis. These findings will inform widespread rollout of our bronchiolitis interventions, and guide future practice change in acute care settings. TRIAL REGISTRATION: Australian and New Zealand Clinical Trials Registry: ACTRN12616001567415 .
© The Author(s) 2021
Keywords: 0807 Library and Information Studies; 1110 Nursing; 1117 Public Health and Health Services